β‑glucan vaccine adjuvant approach for cancer treatment through immune enhancement (B‑VACCIEN) in specific immunocompromised populations (Review) - Ikewaki, Nobunao; Dedeepiya, Vidyasagar; Raghavan, Kadalraja; Rao, Kosagi-Sharaf; Vaddi, Suryaprakash; Osawa, Hiroshi; Kisaka, Tomohiko; Kurosawa, Gene; Srinivasan, Subramaniam; Kumar, Seydunganallu; Senthilkumar, Rajappa; Iwasaki, Masaru; et al. (Oncology reports, 2022)
The incidence of cancer, which is the second leading cause of mortality globally, continues to increase, although continued efforts are being made to identify effective treatments with fewer side‑effects. Previous studies have reported that chronic microinflammation, which occurs in diseases, including diabetes, along with weakened immune systems, may ultimately lead to cancer development. Chemotherapy, radiotherapy and surgery are the mainstream approaches to treatment; however, they all lead to immune system weakness, which in turn increases the metastatic spread. The aim of the present review was to provide evidence of a biological response modifier β‑glucan [β‑glucan vaccine adjuvant approach to treating cancer via immune enhancement (B‑VACCIEN)] and its beneficial effects, including vaccine‑adjuvant potential, balancing metabolic parameters (including blood glucose and lipid levels), increasing peripheral blood cell cytotoxicity against cancer and alleviating chemotherapy side effects in animal models. This suggests its value as a potential strategy to provide long‑term prophylaxis in immunocompromised individuals or genetically prone to cancer.